Sistem Kontrol Kipas Angin Menggunakan Smartphone Berbasis Android Dengan Mikrokontroler NodeMCU ESP8266 (Studi Kasus : SD Negeri Babakan 02) - Sifa Nur Faujiah; Hadi Zakaria (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
An abstract Babakan 02 State Elementary School is one of the public elementary schools in Bogor Regency. Babakan 02 State Elementary School has 6 classes and 1 office room where each class and room is provided with a fan. However, the fan facilities provided are still not optimal in operation, because for its operation it takes school guards to turn on or turn off the fan facilities. To overcome this problem, the author conducted research to create a control system for fan facilities using an Android-based smartphone with an Arduino Uno R3 microcontroller. The fan control system developed is a technological development that can make it easier for users to control the fan remotely by installing a microcontroller into the fan system so that it can be controlled in Android using the wifi feature. The microcontroller used in the fan control system is the Nodemcu Esp8266 microcontroller which functions as a data processor from sensor input and regulates relay work. It is expected that the fan control system using an Android-based smartphone with the Nodemcu Esp8266 microcontroller can facilitate the operation of the fan at SD Negeri Babakan 02, so that the use of fans can be more efficient and save energy.